Health Related Quality of Life (HRQoL) in Type 2 Diabetes Mellitus Patients Based on Antidiabetic Prescription Patterns - Seftika Sari; Erniza Pratiwi; Dinda Farahdilla; MT Ghozali; Indriyati Hadi Sulistyaningrum; Prasojo Pribadi (Sanata Dharma University, 2025)
Diabetes mellitus is characterized as a multifaceted metabolic disorder marked by elevated blood sugar levels or hyperglycemia. Among its types, type 2 diabetes mellitus is the most common globally, significantly affecting a large portion of the population. In Indonesia, there has been a notable increase in the prevalence of type 2 diabetes, indicating a rising trend. This condition necessitates continuous care and management since it is incurable, requiring patients to undergo lifelong treatment. The various therapeutic approaches available for managing type 2 diabetes have a significant impact on the quality of life of patients, highlighting the necessity for quality-of-life assessments. The primary objective of this study was to assess the quality of life among individuals diagnosed with type 2 diabetes mellitus. It also aimed to investigate the effects of different patterns of antidiabetic drug prescriptions on the Health-Related Quality of Life (HRQoL), employing the Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ) for evaluation. This study was conducted as a quantitative, observational research using a cross-sectional approach and a descriptive analytical method. A total of 99 participants were included through purposive sampling, a non-probability sampling technique. The findings showed that the average quality of life score was 70.56, with 48 participants (48.5%) reported to have a good quality of life and 51 (51.5%) considered to have a poor quality of life. Importantly, significant results (p0.05) were found regarding the positive effects of combining oral antidiabetic drugs with insulin on enhancing the quality of life in individuals with type 2 diabetes, underscoring the influence of medication regimens on patient health outcomes.